Short-Term Music Training Enhances Verbal Intelligence and Executive Function - Moreno, Sylvain; Bialystok, Ellen; Barac, Raluca; Schellenberg, E. Glenn; Cepeda, Nicholas J.; Chau, Tom (Psychological Science, 2011)
Researchers have designed training methods that can be used to improve mental health and to test the efficacy of education programs. However, few studies have demonstrated broad transfer from such training to performance on untrained cognitive activities. Here we report the effects of two interactive computerized training programs developed for preschool children: one for music and one for visual art. After only 20 days of training, only children in the music group exhibited enhanced performance on a measure of verbal intelligence, with 90% of the sample showing this improvement. These improvements in verbal intelligence were positively correlated with changes in functional brain plasticity during an executive-function task. Our findings demonstrate that transfer of a high-level cognitive skill is possible in early childhood.